Resources Supporting Incorporeal Assets in Continuously Traded Philippine Universal Banks - Tan, Jackson Juatco; Arceo, Virginia Ramirez (UUM Press, 2024)
The Strengthening Program for Rural Banks (SPRB) in the Philippines has allowed universal banks to purchase rural banks, and this policy highlights the possible advantages of expanding business combinations for intangible assets. Considering the SPRB, this paper examines the intangible motivation behind banks’ actions to purchase capital-deficient financial institutions. This study aims to address sources of intangible assets for Philippine banks as Tobin’s q measures. Using Tobin’s q as a measure of intangible value allows for identifying contributing factors that determine it based on financial data. The study subjects are actively traded Philippine Universal Banks between 2009 and 2018. The influence of variables in the study on intangible asset value, as Tobin’s q measures, was determined using an Ordinary Least Squares model. Operational factors significantly influencing intangible value are investments in subsidiaries and associates, the return on assets, and bank deposits. Activities intended to reach target customers, such as those captured by marketing and advertising expenditures, positively influence intangible value. These findings imply that merely purchasing more assets does not improve the value of intangible resources. Instead, asset productivity, funds to make more loans, and informing the public of bank activities benefit intangible asset values. The implications of these findings offer insight into the sources of intangible assets that investors value